2017–2018 Florida Citrus Production Guide: Grove Planning and Establishment - Mongi Zekri; Ute Albrecht; Christopher Vincent; Tripti Vashisth (EDIS)
Many factors need to be considered when preparing for new tree plantings. Careful planning and preparation is necessary to ensure success and reduce future frustrations. This 3-page document describes the factors that contribute to the success of new grove establishment. Written by Mongi Zekri, Ute Albrecht, Christopher Vincent, and Tripti Vashisth, and published by UF’s Horticultural Sciences Department, July 2017.